The Performance Of The National Narcotics Agency In Illegal Drugs Prevention Efforts Of Palu City, Central Sulawesi, Indonesia - Andi Pasinringi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2020)
This study aims to determine the performance of Badan Narkotika Nasional or the National Narcotics Agency of Palu in the narcotics prevention efforts, determined by the support of the main tasks and functions of the National Narcotics Agency Office of Palu. The theory used to assess performance is with five dimensions of theory to measure the performance of public bureaucracy which are Productivity, Service Quality, Responsiveness, Responsibility, and Accountability as proposed by Agus Dwiyanto (2002). This research utilized descriptive-qualitative approach. Data collection techniques used are but not limited to: Observation, Interview, and Documentation. Informants in this study are determined purposively. The results of the study revealed that based on the five dimensions of performance theory from Agus Dwiyanto, it can be concluded that the performance of the National Narcotics Agency of Palu is not insufficient. Thus, the vision proclaimed by the Palu City Government which was the Realization of Government and Community Synergy Towards Drug-Free Palu City in 2015, was not achieved